The Mediating Role of Moral Disengagement in Predicting Deviant Workplace Behavior Among Nurses in Malaysia - Maslina Mansor; Asyraf Afthanorhan; Rashidah Mohd Ibrahim; Ahmad Munir Mohd Salleh (Iran University of Medical Sciences, 2023)
Background: The healthcare environment is becoming increasingly competitive to meet patients' expectations and demands. Despite the nurses' best efforts to provide the finest services, they often receive complaints from people dissatisfied with the services they receive. There are reports claiming nurses as violent and unethical in their duties. This condition causes constant stress among nurses, translating into trait anger and negative affect. The present work aimed to examine the influence of trait anger and negative affectivity on deviant workplace behavior with the mediating role of moral disengagement.  Methods: This cross-sectional correlational study was conducted in the general hospitals of the northern, southern, east coast, and central Malaysia's regions from January to June 2020. The study sample included 387 nurses recruited by proportionate stratified random sampling. The data were collected using negative affect scale, deviant workplace behavior scale, trait anger scale, and moral disengagement scale. Then, the obtained were analyzed using partial least squares path modeling (PLS-PM) with SMART PLS software, version 3.2.8. Results: The results of the PLS-PM suggested that trait anger contributes to deviant workplace behavior (β=0.245, P=0.001). Also, this study discovered that moral disengagement mediates the relationship between trait anger, negative affectivity, and deviant workplace behavior among nurses.  Conclusion: This study enriches the knowledge of deviant workplace behavior in healthcare settings, specifically Malaysia's public healthcare sector. In the future, similar studies should be performed in private hospitals to improve the generalisability of the findings.